Preschool Participation and BMI at Kindergarten Entry: The Case for Early Behavioral Intervention - Meghan E. McGrady; Monica J. Mitchell; Sarah N. Theodore; Brian Sersion; Elizabeth Holtzapple (Journal of Obesity)
Preschool years (ages 3–5) are a critical period in growth and development. Emerging studies suggest that preschool attendance may be linked to future weight, and perhaps obesity. This study examined relationships between public preschool attendance, demographic variables, and weight at kindergarten entry. Participants included 2,400 children entering kindergarten in 2006. Height and weight were used to calculate a child's BMI category based on CDC norms. At kindergarten entry, 17% of participants were overweight, and 18% were obese. Children attending a public preschool were at an increased risk for overweight (OR=1.06) and obesity (OR=1.34) at kindergarten entry, χ2(2)=6.81, P=.03 relative to children who did not attend preschool. No significant trends relationships between demographics and weight status were found, but demographic variables are summarized descriptively. Policy and clinical implications are provided.